Contabilidade interorganizacional: um estudo envolvendo empresas de Campina Grande - PB - Galvão, Diego Mentor Andrade (2018)
Over the years, companies have experimented with new ways of relating to each other, developing novel methods of coordination, relationship and cooperation. Accounting in its traditional forms no longer satisfied the need to provide information to its users, since it was restricted to the reality of a company in isolation, needing to overcome these barriers to achieve those goals. In this context, the concept of interorganizational accounting emerges, a set of practices aimed at the sharing of accounting and management information between participating companies in order to obtain mutual benefits. Thus, the present research was carried out in order to verify an association between the profile of the managers and industries and the practice of interorganizational accounting within the businessrelationships of Campina Grande - PB. As a methodology, a survey of 32 questions was utilized. Data analysis was performed through descriptive statistics based on frequency observation and inferential analysis based on general purpose hypothesis tests using the IBM SPSS statistical software (version 20) and the Cramer V test with significance level of 5%. The research revealed most companies do not share information in their buyer-supplier relationship. However, among the companies that did share, the majority of information came from suppliers to buyers. From the hypothesis test, factors of the managers' profiles associated to the practice of interorganizational accounting were perceived, namely the educational training of the manager and their relationship to the company. Companies with hired managers were more likely to share information than those managed by business owners. Some characteristics of the companies, such as the duration of the contract, the activity sector and the size of the companies were also associated with interorganizational accounting practices. Companies that have an implanted Supply Chain Management sector tend to share more information than those that do not. Similarly, larger company size corresponded with a greater tendency to share information. The research also found an association between information sharing and the number of perceived benefits. Additionally, an association was found between the existence of a supply chain sector, the duration of the contract and the size of the company with the volume of benefits perceived.